Pengelolaan Arsip Dinamis - Wardah, Mutiawatul (LIBRIA, 2016)
Archives have a very important role in many aspects of life. Beside as an information source, an archive is also an authentic evidence that can be accounted for righteousness. Therefore, the authors of this paper focus on "Dynamic Archive Management". The purpose of this paper is to know the management of records that can feedback deeper understanding about the management of records. Furthermore, this paper is the study of literature supporting character in the answer the problem in writing. Basically, the archive function is divided into archives and records. The archives are not used in everyday activities while the records used in daily activities. Records are divided into three types; active, semi- active and inactive records. The Urgency of records must not be separated in the management of systematic records that have been regulated in Law No. 43 of 2009 which includes the creation, use and maintenance, and depreciation archives.